2006
DOI: 10.1016/j.str.2006.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in the Lectin Domain of CD23, the Low-Affinity IgE Receptor, upon Calcium Binding

Abstract: CD23, the low-affinity receptor for IgE (Fc epsilonRII), regulates IgE synthesis and also mediates IgE-dependent antigen transport and processing. CD23 is a unique Fc receptor belonging to the C-type lectin-like domain superfamily and binds IgE in an unusual, non-lectin-like manner, requiring calcium but not carbohydrate. We have solved the high-resolution crystal structures of the human CD23 lectin domain in the presence and absence of Ca2+. The crystal structures differ significantly from a previously determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
67
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 49 publications
7
67
2
Order By: Relevance
“…The NMR structure reveals a striking distribution of acidic and basic residues on opposites faces of the lectin head domain and demonstrates unequivocally that the interaction surfaces for IgE and CD21 binding are spatially distinct (14); the data also support unequivocally earlier studies that suggested that these binding sites and the structures responsible for expression of cytokine-like activities are distinct (16). The crystal structure confirms that CD23 contains only a single calcium binding site in the lectin head and that conformational changes in the CD23 structure accompany calcium coordination in this site (15). The binding site for integrins was not identified in either study, and, as reported here, this resides at the N-terminal region of the C-type lectin domain.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The NMR structure reveals a striking distribution of acidic and basic residues on opposites faces of the lectin head domain and demonstrates unequivocally that the interaction surfaces for IgE and CD21 binding are spatially distinct (14); the data also support unequivocally earlier studies that suggested that these binding sites and the structures responsible for expression of cytokine-like activities are distinct (16). The crystal structure confirms that CD23 contains only a single calcium binding site in the lectin head and that conformational changes in the CD23 structure accompany calcium coordination in this site (15). The binding site for integrins was not identified in either study, and, as reported here, this resides at the N-terminal region of the C-type lectin domain.…”
supporting
confidence: 85%
“…In association with interleukin-1␣, sCD23 promotes differentiation of monocytes and early thymocyte precursors (11) and, via binding to the ␣M␤2 (CD11b-CD18), ␣X␤2 (CD11c-CD18) (12), and ␣v␤3 integrins (13), stimulates tumor necrosis factor-␣ and interleukin-1␣ production by monocytes. The structures of the derCD23 protein, a naturally occurring sCD23 fragment generated by action of the derp1 protease from Dermatophagoides pteronyssinus, and of a 25-kDa sCD23 (residues 150 -321), have recently been solved by heteronuclear nuclear magnetic resonance spectroscopy (14) and x-ray crystallography (15), respectively. Although there are pronounced differences between the structures derived by the two methods, both show a generally consistent overall structure for the C-type lectin head domain comprising eight ␤ sheets and two ␣ helices (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the existence of a disordered loop in derCD23 at the edge of the interface [residues 256-257 of loop 4, following earlier terminology (40)] is intriguing. The crystal structure of the lectin head domain showed Ca 2+ bound at a site involving residues Glu249 and Thr251 of loop 4 (40). In that structure, residues 253-257 of loop 4 were also disordered, paradoxically becoming ordered in the absence of Ca 2+ owing to a rearrangement of the side chain of Arg253, which occupied the Ca 2+ site.…”
Section: Discussionmentioning
confidence: 97%
“…A crystal structure of the head domain with a single bound Ca 2+ ion has been solved, together with the Ca 2+ -free form (40), and an NMR structure also reports Ca 2+ binding, but at an alternative site (6). However, no Ca 2+ ions were observed in any of the six derCD23 molecules in the Fcε3-4 complex, despite the presence of 2 mM Ca 2+ in the crystallization medium.…”
Section: Discussionmentioning
confidence: 99%